Особливості формування облікової політики щодо афілійованих осіб - Клименко, Я. В.; Klymenko, Ya. (ЦНТУ, 2019)
У статті проаналізовано нормативну базу України з питань формування облікової політики щодо операцій з пов’язаними особами, узагальнено підхід до визначення афілійованих сторін та характеру стосунків між ними. Особливу увагу приділено дослідженню вимог законодавства щодо критеріїв необхідності складання консолідованої фінансової звітності та відображення даних про операції з пов’язаними особами у примітках до фінансової звітності, їх вплив на визначення облікової політики підприємства. В статье проведен анализ нормативной базы Украины по вопросам формирования учетной политики в отношении операций со связанными лицами, обобщен подход к определению аффилированных сторон и характера отношений между ними. Особое внимание уделено исследованию требований законодательства относительно критериев необходимости составления консолидированной финансовой отчетности и отражения данных об операциях со связанными лицами в примечаниях к финансовой отчетности, их влияние на определение учетной политики предприятия. In the conditions of transition of economy of Ukraine to the accounting system in accordance with national provisions (standards) of accounting, economic entities are given some autonomy and choice of alternatives when deciding on the choice of principles, methods and procedures used in reporting. An important prerequisite for an effective accounting and reporting system is to determine and shape the company's accounting policies. The purpose of accounting policies is to streamline the accounting process, to provide complete, reliable and impartial information for effective management. The enterprise independently develops an accounting model that provides information about the activity of the enterprise for all interested users. Choosing an accounting policy requires the development of an appropriate regulatory document (for example, an order). This applies to all businesses, including those related to other entities. The criterion of the need, in accordance with the requirements of the legislation, to submit consolidated financial statements is important in accounting policy making. To this end, the article analyzes the requirements of the legislation to differentiate the criteria for the need to prepare and consolidate financial statements and to show related party transactions in the notes to the financial statements. One of the elements of an enterprise's accounting policy is to establish the principles for the classification of related parties and their list, taking into account the materiality of the relationship. The process of identifying related parties to reflect in accounting policies requires significant work to be done and to analyze both the relationships within the entity and the main contractors, as well as identify entities that have direct and indirect ownership, significant control and control over their subjects of activity. For clarity, the article provides an example of formulating the main points of an accounting policy order to display affiliate information.
Особенности формирования учетной политики в отношении аффилированных лиц
Features of Formation of Accounting Policy for Affiliates
Keywords: афілійовані особи; пов’язані особи; контроль; суттєвий вплив; звітність; облікова політика; аффилированные лица; связанные лица; контроль; существенное влияние; отчетность; учетная политика; affiliates; related parties; control; significant influence; reporting; accounting policy